2017
DOI: 10.1016/j.jtho.2016.11.926
|View full text |Cite
|
Sign up to set email alerts
|

P1.07-015 STOMP: A UK National Cancer Research Network Randomised, Double Blind, Multicentre Phase II Trial of Olaparib as Maintenance Therapy in SCLC

Abstract: Background: While there is no approved third line chemotherapy option for small cell lung cancer (SCLC), empiric use of chemotherapy is common in this setting in the absence of supporting prospective data. In order to assess the potential benefit and predictors of chemotherapy use beyond the second line setting in SCLC, we analyzed the SEER-MEDICARE database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…In total, 1,957 patients from eight RCTs 7 9 , 17 21 were available for the meta-analysis, of whom 786 had ovarian cancer, 7 , 18 20 302 breast cancer, 9 649 gastric cancer, 8 , 17 and 220 small-cell lung cancer (SCLC). 21 Of the included studies, three were Phase III RCTs 7 9 and five were Phase II RCTs. 17 21 All studies reported sufficient data on PFS 7 9 , 17 21 and OS, 7 9 , 17 21 and six reported sufficient data on ORR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 1,957 patients from eight RCTs 7 9 , 17 21 were available for the meta-analysis, of whom 786 had ovarian cancer, 7 , 18 20 302 breast cancer, 9 649 gastric cancer, 8 , 17 and 220 small-cell lung cancer (SCLC). 21 Of the included studies, three were Phase III RCTs 7 9 and five were Phase II RCTs. 17 21 All studies reported sufficient data on PFS 7 9 , 17 21 and OS, 7 9 , 17 21 and six reported sufficient data on ORR.…”
Section: Resultsmentioning
confidence: 99%
“… 21 Of the included studies, three were Phase III RCTs 7 9 and five were Phase II RCTs. 17 21 All studies reported sufficient data on PFS 7 9 , 17 21 and OS, 7 9 , 17 21 and six reported sufficient data on ORR. 8 , 9 , 17 20 Additionally, five trials reported sufficient data on efficacy of olaparib in patients with BRCA mutations, 7 , 9 , 18 20 and two trials reported efficacy data in patients with ATM deficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-agent olaparib was tested as maintenance therapy after completion of frontline chemotherapy in the Surveillance or Metastasis-Directed Therapy for Oligometastatic Prostate Cancer Recurrence (STOMP) trial but did not show any clinical benefit in comparison with placebo. 30 The combination of olaparib and temozolomide, however, showed promising activity in relapsed SCLC, whereas the combination of veliparib and temozolomide showed efficacy only in subset of patients with relapsed SCLC who had with SLFN11 expression. 31,32 Although the initial result of our study is promising, additional confirmation in a larger definitive study is warranted, given the mixed results reported by other studies of PARP inhibitors in this patient population.…”
Section: Discussionmentioning
confidence: 97%
“…PARP inhibitors are also being investigated in the maintenance setting in patients with SCLC, who have not progressed after first line chemotherapy or chemoradiation. The phase 2 STOMP trial, showed no significant benefit of olaparib as a maintenance treatment compared to placebo [57]. In an ongoing phase 3 trial, niraparib is being compared to placebo as maintenance therapy in Chinese patients with ES-SCLC [58].…”
Section: Dna Damage Response Targetingmentioning
confidence: 99%